2013
DOI: 10.2478/v10298-012-0091-9
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Management Studies in Maize (Zea Mays L.) Hybrids

Abstract: A field experiment was conducted to study the effect of different nitrogen management methods on yield, yield components and quality attributes of maize hybrids (single cross-6142 and double cross-4444) under irrigated conditions. Nitrogen dose is met either by PM (poultry manure) or urea according to each treatment. PM was incorporated at the time of presowing irrigation whereas fertigation method at knee height stage and foliar spray at flowering were use for the application of urea. Results showed that plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The NPs efficiency is determined by their chemical composition, surface covering, size, reactivity, and the most importantly is the dose which they are effective (Khodakovskaya et al, 2012). The increases in these characters because of partial replace of conventional urea with nano urea could be attributed to nano fertilization increases availability of nutrient to the growing plant (Hediat & Salama, 2012) and reduced losses of conventional N (Wu & Liu, 2008;Iqbal et al, 2013). The nano-fertilizers have higher surface and reactive area it is mainly due to very less or smallest size of particles which provide more sites to facilitate different metabolic process in the plant system result production of more photosynthesis and intern more growth and yield (Qureshi et al, 2018).…”
Section: Maize Charactersmentioning
confidence: 99%
See 2 more Smart Citations
“…The NPs efficiency is determined by their chemical composition, surface covering, size, reactivity, and the most importantly is the dose which they are effective (Khodakovskaya et al, 2012). The increases in these characters because of partial replace of conventional urea with nano urea could be attributed to nano fertilization increases availability of nutrient to the growing plant (Hediat & Salama, 2012) and reduced losses of conventional N (Wu & Liu, 2008;Iqbal et al, 2013). The nano-fertilizers have higher surface and reactive area it is mainly due to very less or smallest size of particles which provide more sites to facilitate different metabolic process in the plant system result production of more photosynthesis and intern more growth and yield (Qureshi et al, 2018).…”
Section: Maize Charactersmentioning
confidence: 99%
“…The results obviously indicated that 75% N mineral + 25% N nano treatment recorded the highest values of these characters, while application of 100% nano urea alone was the lowest once and not suitable for application. The increases in these characters due to the combination between nano and mineral fertilization at different percent of its recommended could be attributed to nano fertilization increase availability of nutrient to the growing plant (Hediat & Salama, 2012) and reduced losses of conventional N (Wu & Liu, 2008;Iqbal et al, 2013). Consequently, meristematic activity, stimulation of cell elongation and production of cowpea increased.…”
Section: Effect Of N Nano-mineral Fertilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…(Mahgoub and El-Shenawy (2005) and El-Galfy et al, 2009). The authors including Azam et al, (2007) and Iqbal et al, (2013) concluded Similar conclusion with respect to cob weight. Shelling percentage was repeated as a different among crosses; Mekkei (1995); Afifi and Khattab, 2011 ) and Iqbal et al, (2013).…”
Section: Resultsmentioning
confidence: 60%
“…The grain yield and protein in maize are highly dependent on fertilizer consumption. Today, however, the use of chemical fertilizers has expanded dramatically as the fastest way to compensate for soil nutrient deficiencies and high yields, but in many cases, the use of these fertilizers causes environmental pollution and ecological damage and increases production cost (Hearn 2014;Iqbal et al 2013;Dibaba et al 2013). Sprouts of kernels are one of the most valuable parts of the maize.…”
Section: Introductionmentioning
confidence: 99%